1995
DOI: 10.3109/00016349509024400
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mRNA for keratinocyte growth factor and its receptor in human endometrium

Abstract: The results suggest that keratinocyte growth factor mRNA expression is progesterone dependent, whereas keratinocyte growth factor receptor mRNA expression seems to be more estrogen than progesterone dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…5759 In the uterus, KGF expression is lowest during the proliferative phase (predominantly estradiol) and highest during the secretory phase (predominately progesterone). 58, 59 Previous work from our laboratory has shown that, in vitro , estradiol inhibits mouse uterine epithelial cell constitutive, as well as LPS-induced, CCL20 secretion. 44 More recently, our laboratory has demonstrated that CCL20 and CXCL1 fluctuate during the estrous cycle of the mouse.…”
Section: Introductionmentioning
confidence: 99%
“…5759 In the uterus, KGF expression is lowest during the proliferative phase (predominantly estradiol) and highest during the secretory phase (predominately progesterone). 58, 59 Previous work from our laboratory has shown that, in vitro , estradiol inhibits mouse uterine epithelial cell constitutive, as well as LPS-induced, CCL20 secretion. 44 More recently, our laboratory has demonstrated that CCL20 and CXCL1 fluctuate during the estrous cycle of the mouse.…”
Section: Introductionmentioning
confidence: 99%
“…Due to ligand and receptor expression patterns, it is thought that KGF functions as a paracrine mediator of stromal fibroblast-epithelial cell interactions [73,78,79]. Stage of the menstrual cycle influences the expression of KGF and KGFR in the human and primate endometria suggesting that KGF is under hormonal control [79][80][81]. KGF expression appears to be lowest during the proliferative phase and peaks during the late-secretory phase [80,81].…”
Section: Keratinocyte Growth Factormentioning
confidence: 99%
“…Stage of the menstrual cycle influences the expression of KGF and KGFR in the human and primate endometria suggesting that KGF is under hormonal control [79][80][81]. KGF expression appears to be lowest during the proliferative phase and peaks during the late-secretory phase [80,81]. In contrast to KGF expression in the endometrium, mammary gland treatment with E 2 increases KGF mRNA expression in a dose-dependent manner while progesterone is needed to stabilize KGFR mRNA [78,82].…”
Section: Keratinocyte Growth Factormentioning
confidence: 99%
“…The same applies to the expression of heparin-binding epidermal growth factor (Zhang et al 1994). Studies indicate that keratinocyte growth factor is a progestomedin expressed by stromal cells, whereas expression of its receptor is estrogen-dependent (Koji et al 1994, Siegfried et al 1995. Recent results suggest that progesterone is also a potent stimulator of basic fibroblast growth factor in the rat uterus (Rider et al 1997).…”
Section: Introductionmentioning
confidence: 97%